Gitelman syndrome associated with chondrocalcinosis and severe neuropathy: a novel heterozygous mutation in SLC12A3 gene - E. Conticini; A. Negro; L. Magnani; R. Ugolini; B. Atienza-Mateo; B. Frediani; C. Salvarani (PAGEPress Publications, 2020)
Gitelman syndrome (GS) is an inherited salt-wasting tubulopathy characterized by hypocalciuria, hypokalemia, hypomagnesemia and metabolic alkalosis, due to inactivating mutations in the SLC12A3 gene. Symptoms may be systemic, neurological, cardiovascular, ophthalmological or musculoskeletal. We describe a 70 year-old patient affected by recurrent arthralgias, hypoesthesia and hyposthenia in all 4 limbs and severe hypokalemia, complicated by atrial flutter. Moreover, our patient reported eating large amounts of licorice, and was treated with medium-high dosages of furosemide, thus making diagnosis very challenging. Genetic analysis demonstrated a novel heterozygous mutation in the SLC12A3 gene; therefore, we diagnosed GS and started potassium and magnesium replacement. GS combined with chondrocalcinosis and neurological involvement is quite common, but this is the first case of an EMG-proven severe neuropathy associated with GS. Herein, we underline the close correlation between hypomagnesemia, chondrocalcinosis and neurological involvement. Moreover, we report a new heterozygous mutation in exon 23 (2738G>A), supporting evidence of a large genetic heterogeneity in this late-onset congenital tubulopathy.